Development and characterization of phytosomes containing aegle marmelos (bael) - Rajendra; Kumar, Kapil; Joshi, Aparna; Negi, Anjali; Rajput, Vaishali (International Journal of Indigenous Herbs and Drugs, 2023)
Aegle marmelos, commonly known as Bael, is a medicinal plant with a wide range of pharmacological properties. However, its therapeutic potential is often limited by its poor bioavailability due to low water solubility and inefficient absorption. Phytosomes, a novel drug delivery system, have emerged as a promising approach to improving the bioavailability and efficacy of herbal extracts. In this study, we aimed to develop and characterize phytosomes containing Aegle marmelos extract for enhanced therapeutic benefits. The phytosomes were prepared using a solvent evaporation technique, where phospholipids were complexed with the Aegle marmelos extract. The formulation was evaluated using various ratios of phospholipids and extract to achieve maximum entrapment efficiency and drug-loading capacity. The resulting phytosomes were then characterized for their physicochemical properties, including particle size, zeta potential, and morphology using techniques such as dynamic light scattering and transmission electron microscopy. Furthermore, the in vitro release profile of the Aegle marmelos phytosomes was evaluated using a dissolution apparatus to determine their sustained release behavior. The improved dissolution profile indicated prolonged drug release, suggesting enhanced bioavailability and potential for reduced dosing frequency. In conclusion, our study successfully developed and characterized phytosomes containing Aegle marmelos extract, showing improved bioavailability and enhanced cellular uptake. These findings indicate the potential of phytosomes as a promising drug delivery system to optimize the therapeutic benefits of Aegle marmelos and potentially other herbal extracts.Keywords: Phytosomes, extract, evaluation.